2015
DOI: 10.1152/jn.00414.2015
|View full text |Cite
|
Sign up to set email alerts
|

Changes in sensory reweighting of proprioceptive information during standing balance with age and disease

Abstract: With sensory reweighting, reliable sensory information is selected over unreliable information during balance by dynamically combining this information. We used system identification techniques to show the weight and the adaptive process of weight change of proprioceptive information during standing balance with age and specific diseases. Ten healthy young subjects (aged between 20 and 30 yr) and 44 elderly subjects (aged above 65 yr) encompassing 10 healthy elderly, 10 with cataract, 10 with polyneuropathy, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
52
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 64 publications
9
52
0
1
Order By: Relevance
“…In addition to experiencing an overall increase in the challenge of controlling balance, older adults appear to be less able to adapt balance control to varying environmental conditions (Pasma et al 2015). Young adults were shown to down-modulate the soleus H-reflex between prone and standing, while older adults showed no modulation (Koceja and Mynark 2000) or even up-modulation with postural demands (Koceja et al 1995;Angulo-Kinzler et al 1998).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to experiencing an overall increase in the challenge of controlling balance, older adults appear to be less able to adapt balance control to varying environmental conditions (Pasma et al 2015). Young adults were shown to down-modulate the soleus H-reflex between prone and standing, while older adults showed no modulation (Koceja and Mynark 2000) or even up-modulation with postural demands (Koceja et al 1995;Angulo-Kinzler et al 1998).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…In upright stance, balance is challenged by gravity and the relatively high position of the body center of mass (CoM) over a small base of support. This challenge increases with impairments in neuromuscular control resulting from age or disease (Pasma et al 2015). But even for young, healthy individuals, maintenance of balance can become challenging when their base of support is reduced or when compliance of the surface which they are standing on is increased (Raymakers et al 2005;Schut et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The impact on patients is comparable with that of major systemic conditions including stroke, diabetes, and arthritis. In a study in patients with cataract, Pasma et al found a higher proprioceptive weight compared with healthy elderly participants, which means that the elderly with cataract rely more on their proprioceptive information [7].…”
Section: Cataractmentioning
confidence: 99%
“…Systems can partially compensate for each other's deterioration. Failing compensation strategies may eventually result in impaired balance, which may result in falls [7].…”
Section: Postural Balancementioning
confidence: 99%
“…The coherent internal body scheme is also a reference frame to which somatosensory information is compared in order to interpret changes in body segments or upright posture (Proske & Gandevia, 2012). Ageing affects the ability to flexibly reweight proprioceptive information and this will contribute to an increased risk of falls (Eikema et al, 2013;Pasma et al, 2015). Testing balance control with different sensory challenges, such as combinations of eye closure and difference in support surface compliance has been used to evaluate balance function with ageing and neurological disorders (Horak, 1997;Sturnieks et al, 2008) and could highlight age-related issues in the ability to dynamically reweight sensory information which could underpin falls risk.…”
Section: Age-related Changes In the Sensory Systemmentioning
confidence: 99%